A novel highly selective and stable Ag/MgO-CeO2-Al2O3 catalyst for the low-temperature ethanol-SCR of NO - Valanidou, Lilian; Theologides, Christodoulos P.; Zorpas, Antonis A.; Savva, Petros G.; Costa, Costas (My University, 2011)
The selective catalytic reduction of NO by ethanol under strongly oxidizing conditions (ethanol-SCR) in the wide-temperature range of 150–400 °C has been studied over Ag supported on a series of metal oxides (e.g., MgO, Y2O3, CuO, CeO2, SiO2, MgO-CeO2-Al2O3). The Ag/MgO, Ag/CeO2 and Ag/Al2O3 solids showed the best catalytic behavior with respect to N2 and CO2 yield and the widest temperature window of operation compared with the other single metal oxide-supported Ag solids. An optimum 25 wt% MgO-25 wt% CeO2-Al2O3 support composition was found in terms of specific reaction rate of N2 production (mol N2/gcat s) and CO2 selectivity. High NO conversions (60–90%), N2 selectivities (95–99%) and CO2 selectivities (>97%) were also obtained in the 150–400 °C range at a GHSV of 40,000 h−1 with the low 0.1 wt% Ag loading and using a feed stream of 0.05 vol% NO, 0.1 vol% ethanol, 5 vol% O2, 5 vol% H2O and He as balance gas. Moreover, the latter catalytic system exhibited a high stability in the presence of 50 ppm SO2 in the feed stream. N2 selectivity values higher than 98% and CO2 selectivities higher than 97% were obtained over the 0.1 wt% Ag/MgO-CeO2-Al2O3 catalyst in the 150–400 °C range in the presence of water and SO2 in the feed stream. The above-mentioned results led to the submission of a patent application for the commercial exploitation of Ag/MgO-CeO2-Al2O3 catalyst towards a new NOx control technology in the low-temperature range of 150–250 °C using ethanol as reducing agent. DRIFTS studies after adsorption of NO, and transient titration of the adsorbed surface intermediate NOx species with H2 experiments, have revealed some preliminary important information towards the understanding of basic mechanistic issues of the present catalytic system (e.g., number and location of possible active NOx intermediate species).
Keywords: Ethanol-SCR; Lean de-NOx; NO reduction; DRIFTS; Supported-Ag